2010
DOI: 10.1111/j.1530-0277.2010.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Operant Oral Ethanol Self-Administration: A Dose-Response Curve Study in Rats

Abstract: Background-Oral ethanol self-administration procedures in rats are useful pre-clinical tools for the evaluation of potential new pharmacotherapies as well as for the investigation of the etiology of alcohol abuse disorders and addiction. Determination of the effects of a potential treatment on a full ethanol dose-response curve should be essential to predict its clinical efficacy. Unfortunately, this approach has not been fully explored due to the aversive taste reaction to moderate to high doses of ethanol, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 46 publications
2
28
1
Order By: Relevance
“…The most likely explanation is that the mice (temporarily) reduce their ethanol consumption due to the negative/aversive effects produced by repetitive daily binge-like ethanol consumption prior to the development of tolerance. Supporting this possibility, Carnicella and colleague demonstrated a u-shaped ethanol dose response curve in rats' lever pressing for access to ethanol (Carnicella, Yowell, & Ron, 2011). Specifically, the rats progressively increased their response for ethanol until the ethanol concentration reached 10-20%, and as the concentration increased beyond this point, their responding progressively decreased.…”
Section: Interestingly Mccool and Chappell Found Socially Housed Longmentioning
confidence: 79%
“…The most likely explanation is that the mice (temporarily) reduce their ethanol consumption due to the negative/aversive effects produced by repetitive daily binge-like ethanol consumption prior to the development of tolerance. Supporting this possibility, Carnicella and colleague demonstrated a u-shaped ethanol dose response curve in rats' lever pressing for access to ethanol (Carnicella, Yowell, & Ron, 2011). Specifically, the rats progressively increased their response for ethanol until the ethanol concentration reached 10-20%, and as the concentration increased beyond this point, their responding progressively decreased.…”
Section: Interestingly Mccool and Chappell Found Socially Housed Longmentioning
confidence: 79%
“…Conducting the CPP experiment in rats with a history of excessive ethanol (via IA2BC training) provides a more behaviorally relevant way to habituate the animals to ethanol. Furthermore, we showed that similar habituation to ethanol via IA2BC training leads to high ethanol consumption in an operant self-administration procedure (Barak et al, 2013; Carnicella et al, 2008; Carnicella, Yowell, & Ron, 2011) (see below).…”
Section: Intermittent Access To 20% Alcohol In 2-bottle Choicementioning
confidence: 88%
“…Animals consuming less than 4 g/kg/24 h at the baseline are excluded from the study (Carnicella et al, 2008; Carnicella et al, 2011), as they are considered resilient to excessive alcohol intake. Exclusion of rats according to this predefined criterion is critical as rats drinking low levels of ethanol in the IA2BC do not acquire operant 20% ethanol self-administration (S. Carnicella, unpublished observation).…”
Section: Operant Self-administration In Rats Pre-trained In Ia2bcmentioning
confidence: 99%
See 2 more Smart Citations